1000 Basal-Squamous Cell Carcinoma Collision Tumour Of the Preauricular Region. (12th October 2021) - Hallett, G; Holden, A; Colbert, S
Abstract: : Collision tumours are defined as multiple neoplasms adjacent to each other or combined in one area and are particularly rare, with only one other basal-squamous cell carcinoma combination of the head and neck region published in the literature. Case description: An 87-year-old farmer presented to the Maxillofacial Surgery department following referral by his general practitioner concerned with multiple suspected skin neoplasms. Four lesions were identified, two of which required surgical excision with 4mm margins. Following histological investigation, the lesion in the right preauricular area was identified as a basal-squamous cell carcinoma collision tumour which was completely excised with clear margins. Discussion: This case highlights the possibility of multiple skin neoplasms in a single site and gives an insight into the surgical management of a basal-squamous cell carcinoma collision tumour while aiming to increase clinician awareness of collision tumours especially in high-risk sites such as the head and neck. This case suggests that a 4-5mm surgical margin may be sufficient in removing similar presentations of basal-squamous cell carcinoma collision tumours however highlights the importance of appropriate histological examination of specimens not only to correctly diagnose the tumour but to ensure surgical margins are clear to mitigate recurrence risk. It must be noted that systemic metastases are more common in squamous cell carcinoma than in basal cell carcinoma cases and therefore it is possible that basal-squamous cell carcinoma collision tumours may have higher rates of metastases than traditional basal cell carcinomas.